Protocolo de avaliação da qualidade de água de bacias hidrográficas baseado em indicador ambiental: estudo aplicado na sub-bacia hidrográfica do Rio do Campo - Umeki, Kelly Leiko (2020)
Sustainable Development Goal 6 (SDG 6), which deals with “Drinking Water and Sanitation”, consists of eight goals that aim to ensure availability, in quantity and quality, sustainable water and sanitation management for all, whose goals are monitored by indicators. This work has as its central point the goal 6.3, which proposes to assess the water quality conditions of a country by monitoring Indicator 6.3.2 (Proportion of water bodies with good quality). The purpose of this study was to adapt an existing methodology for the indicator in question, using physical-chemical,bacteriological and biological parameters and to classify the water quality according to the worst of the results obtained. The protocol was applied in the Campo river hydrographic sub-basin and the parameters pH, OD, total dissolved solids, total ammoniacal nitrogen, total phosphorus, E. coli and conductivity were evaluated, being subsequently compared with federal legislation for class 2 and conductivity was compared according to the bibliography. The analyzes of the physical-chemical and microbiological results indicated that the sub-basin segments analyzed showed 100% compliance with the legislation, framing the waters of the sample points as of good quality. In relation to biological parameters, the inventoried communities did not present wealth and abundance, resulting in a low score, according to the biological index applied, framing water bodies in the quality range ranging from critical to very critical, this being the final result of the segments of rivers analyzed in the Campo river hydrographic sub-basin. It is noteworthy that, for the benthic macroinvertebrate community, it is not possible to limit wealth and abundance strictly with the water quality, as it depends on other characteristics to be fixed, such as the place substrate and rainfall indexes. In this study, families were found that are sensitive to pollution, attributing the low score to these other factors. The protocol inserted in Appendix A presents a simple methodology and easy to apply, containing the physical-chemical, microbiological and biological water classification.